Proses Morfologis pada Bahasa Madura: Studi pada Mahasiswa Madura di Universitas Trunojoyo - Irfan Irwiandi; Mixghan Norman (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Morphological Processes in the Madurese Language: A Study in Madurese Students at Trunojoyo University.  Researchers aim to know the morphological processes that exist in the Madurese language and as a learning medium for the next generation.  This research uses a descriptive qualitative research method using data collection techniques by communicating directly and observing the speech of Trunojoyo Madura University students. The results showed that morphological p roses are the process of word formation that goes through  the process of affixation (Affixation), the process of  twisting (Duplication)  and komposition in  the M language adura the morphological process is only a process of affixation and duplication.